Cases on consumer-centric marketing management - Jham, Vimi, 1968-; Puri, Sandeep, 1972-; IGI eBooks; IGI Global (Hershey, Pennsylvania (701 E. Chocolate Ave., Hershey, PA, 17033) : IGI Global, 2014)
"This book presents a collection of case studies highlighting the importance of customer loyalty, customer satisfaction, and consumer behavior for marketing strategies"--Provided by publisher.
Understanding consumer behavior through mental accounting: evidence from Turkish consumers / Tugba Ucma, Ali Naci Karabulut, Ali Caglar Uzun -- What went wrong? / Bhavna Bhalla -- Case study on relationship marketing / Bhawana Sharma, Tulika Sood -- A line in water: a case of customer relationship management / Chandra Shekhar Padhi -- The realization of customer satisfaction with technology integrations / Ooi Chien Shing, Seng Kah Phooi, Ang Li-Minn -- Intensive care / Eric Van Genderen -- Always trust the customer: how Zara has revolutionized the fashion industry and become a worldwide leader / Eric Viardot -- Consumer behavior perspective for fairness creams: a case of 'fair & lovely' / Yasser Mahfooz, Faisal Mahfooz -- International branding at Mirza International: dilemma unsolved / Gautam Dutta -- Delhi Bank of India: dilemma of a new bank manager / Sandeep Puri, Jayanthi Ranjan -- Facebook: an application of cloud computing / Lokesh Sharma -- Price effectiveness in hotels: case study comparing strategies adopted by mid-size hotels in New Delhi / Nidhi Chowdhry -- Indian luxury car market changing lanes: a case of BMW India / Pardeep Bawa -- Niche marketing strategies for business growth: an experiential journey / Pradeep Kautish -- Marketing of tobacco products in Australia: dealing with the emerging regulations / Rajeev Sharma -- Concentra BPO: the falling customer satisfaction / Shreya Dhingra -- A case study on customer experiential management at High Five Hotels Pvt. Ltd, Nashik / Sonali Gadekar, Sushil Gadekar -- Case study on customer's ambidextrous nature of trust in internet banking: Australian context / Sujana Adapa, Fredy-Roberto Valenzuela -- Should corporate political lobbying come under scanner by regulatory mechanism?: Vaishnavi corporate communication and 2G spectrum scam / S. Jayachandran -- Tata GoldPlus: adoption of customer oriented strategy for penetrating market opportunity / Salma Ahmed -- When Citi was found sleeping / Suresh Chandra Bihari -- Triumph charter school service provider / Verneshia (Necia) Boone -- Maximizing employee on-boarding: a study in a pharmaceutical company / Shalini Kalia, Neha Mittal, Rohit Arora.
Includes bibliographical references.
Also available in print.
Mode of access: World Wide Web.
Description based on title screen (IGI Global, viewed August 21, 2013).
Keywords: Marketing -- Management -- Case studies; Customer relations -- Case studies; Customer services -- Case studies; Consumer behavior -- Case studies; Cloud computing; Customer relationship management; Customer-focused organizations; Internal marketing; Marketing analytics; Relationship marketing; Electronic books